The Pillory and the cloak: battles of memory between colonial writing and the Tupinamba anticolonial gira - Florencio, Thiago (2025)
In this article, I seek to understand the battles of memory surrounding jesuitic colonial writing and tupinamba anticolonial giras. I connect the formation of colonial writing to the early experiences of catechization by Jesuit Manoel da Nóbrega, whose daily practice of writing letters to his Jesuit brothers, under the doctrine of the Spiritual Exercises, unfolds into the Civilizing Plan (1558)—the first Indigenous-focused legislation that mandated the installation of pillories in settlements and imposed stricter, more violent control over Indigenous bodies. Through this, I aim to demonstrate that Nóbrega’s colonial writing is achieved through the simultaneous attempt to erase Indigenous corporealities and territorialize their bodies. In the second part, I explore how the memory field, which seeks to entrench itself through colonial writing, is contested by Indigenous ritual resistances—embodied in their cloaks and giras—whose modes of existence, grounded in the perspective of spiral time, generate alternative fields of collective memory. These resistances operate beyond the exclusionary dichotomies and capture logics of colonial writing. In this sense, indigenous ritual resistances will take shape, over the course of colonization, as anticolonial giras.